Evaluation of Improving Working Posture Using the Rula and Reba Method in the 3 Kg LPG Cylinder Repair and Maintenance Workshop at PT XYZ - Arifiyah, Nuriyanti; Lukmandono, Lukmandono (International Journal of Science, Engineering, and Information Technology, 2023)
PT XYZ is a private company engaged in the 3 Kg LPG maintenance workshop. Activities within the company include retesting, repairing and repainting 3 Kg LPG cylinders. Workers' activities while working sometimes do not pay attention to safety and comfort at work, which can have a negative impact on the worker, such as complaints of pain in the worker's body parts or Musculoskeletal Disorders (MSDs). Ergonomic assessment analysis is needed to understand the condition of workers' joint muscle tissue and bone tissue in carrying out their duties, which can reduce the risk of MSDs while increasing worker performance. This study aims to evaluate worker posture and provide improvements to the work posture of pressing ring painting and shoot ballast operators using the Rapid Upper Limb Assessment (RULA) and Rapid Entire Body Assessment (REBA). In the RULA method the work process is at a high level in the screen printing of the bottom of tube 10 so improvements need to be made now. The moderate level is found in the process of pressing hand guard 5 and printing hand guard 5 so improvements need to be made in the near future. In the REBA method, the work process is at a high level in the printing process at the bottom of tube 9, so repairs need to be made immediately. Recommendations or proposed improvements based on RULA and REBA calculations are to make movement changes in the tube body screen printing process, hand guard screen printing. Adding or improving work tools based on anthropometric body measurements, suggestions are given to reduce or resolve problems with complaints of muscle pain in production workers at PT. XYZ